2016
DOI: 10.20944/preprints201612.0099.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioactive Nutrients and Nutrigenomics in Age-Related Diseases

Abstract: The increase in the average lifespan and the consequent proportional growth of the elderly segment of society has furthered the interest in studying ageing processes. Ageing may be considered a multifactorial process derived from the interaction between genetic and environmental factors including lifestyle. There is ample evidence in many species that the maximum age attainable (maximum lifespan potential, MLSP) is genetically determined and several mitochondrial DNA polymorphisms are associated with longevity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 107 publications
0
20
0
Order By: Relevance
“…39 Also, most CRC follows the chromosomal instability (CIN) pathway, characterized by widespread loss of heterozygosis (LOH) and gross chromosomal abnormalities. [43][44][45] A prospective cohort study by Iowa Women's Health Study (IWHS) 46,47 have independently shown that cigarette smoking was associated with CIMPpositive tumor, and with BRAF mutated tumor. 40 The authors demonstrated that prediagnosis BMI was associated with an increased risk of developing CRC, which was limited to MSS tumors and that one-carbon metabolism affected CIMP, with tumor epigenetic features modulating the cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…39 Also, most CRC follows the chromosomal instability (CIN) pathway, characterized by widespread loss of heterozygosis (LOH) and gross chromosomal abnormalities. [43][44][45] A prospective cohort study by Iowa Women's Health Study (IWHS) 46,47 have independently shown that cigarette smoking was associated with CIMPpositive tumor, and with BRAF mutated tumor. 40 The authors demonstrated that prediagnosis BMI was associated with an increased risk of developing CRC, which was limited to MSS tumors and that one-carbon metabolism affected CIMP, with tumor epigenetic features modulating the cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…2831 The positive association between dietary inflammatory potential and risk of the colorectal cancer subtype with absent/low peritumoral lymphocytic reaction is biologically plausible. Dietary components exert diverse influences on inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design (49,50) and population-based database allowed us to rigorously investigate the association of tumor PDCD1LG2 expression with lymphocytic reaction to colorectal cancer, controlling for multiple potential confounders. In addition, our colorectal cancer specimens were collected from a large number of hospitals in diverse settings across the U.S., which increases the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%